A randomized trial to investigate the efficacy and safety of once‐daily liraglutide 1.8 mg in Japanese adults with type 2 diabetes exhibiting an inadequate response to liraglutide 0.9 mg. Issue 8 (8th April 2022) - Seino, Yutaka; Miyoshi, Hideaki; Bosch Traberg, Heidrun; Divyalasya, T V S; Nishijima, Keiji; Terauchi, Yasuo
ABSTRACT: Aims/Introduction: The present trial compared the efficacy and safety of once‐daily liraglutide 1.8 mg with liraglutide 0.9 mg in Japanese patients with type 2 diabetes to assess the incremental effects of liraglutide 1.8 mg in those who exhibited an inadequate response to 0.9 mg. Materials and Methods: This 26‐week randomized trial (NCT02505334) enrolled Japanese adults with type 2 diabetes across 47 sites in Japan. Participants with glycated hemoglobin (HbA1c ) 7.5–10.0% were included and those on insulin treatment were excluded. Participants discontinued pre‐trial oral antidiabetic drug and initiated liraglutide 0.9 mg for a 12‐week run‐in period, after which those with HbA1c ≥7.0% (466) were randomized (1:1) to two treatment arms: continuing liraglutide 0.9 mg or dose escalation to 1.8 mg. The change from baseline in HbA1c (primary endpoint) and treatment‐emergent adverse events (secondary endpoint) were measured at the end of 26 weeks. Results: After 26 weeks of treatment, liraglutide 1.8 mg was more effective compared with 0.9 mg in lowering HbA1c levels, with an estimated treatment difference of −0.40% (95% confidence interval [CI] −0.55, −0.24; P  < 0.0001). Liraglutide 1.8 mg was associated with significantly greater odds of participants reaching HbA1c <7.0% (estimated odds ratio [EOR] 3.87; 95% CI 2.12, 7.08; P  < 0.0001) and ≤6.5% (EOR 3.78; 95% CI 1.36, 10.54; P  = 0.0109) compared with 0.9 mg. Both doses were well tolerated. Conclusions: Liraglutide 1.8 mg had better efficacy in improving HbA1c levels after 26 weeks treatment vs 0.9 mg in Japanese patients, with both doses well tolerated. Abstract : This 26‐week randomized trial (NCT02505334) compared the efficacy and safety of once‐daily liraglutide 1.8 mg with liraglutide 0.9 mg in Japanese adults with type 2 diabetes to assess the incremental effects of liraglutide 1.8 mg in those who exhibited an inadequate response to 0.9 mg. The results of this trial demonstrated that liraglutide 1.8 mg had a better efficacy in improving HbA1c levels after 26 weeks treatment vs 0.9 mg in Japanese adults; both doses were well tolerated.